2019
DOI: 10.1371/journal.pone.0222862
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive finger movement and circle drawing in persons with Parkinson’s disease

Abstract: Little is known regarding how repetitive finger movement performance impacts other fine motor control tasks, such as circle drawing, in persons with Parkinson’s disease (PD). Previous research has shown that impairments in repetitive finger movements emerge at rates near to and above 2 Hz in most persons with PD. Thus, the purpose of this study was to compare circle drawing performance in persons with PD that demonstrate impairment in repetitive finger movement and those that do not. Twenty-two participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…We found that most participants without PD had normal or unimpaired motor aptitude levels, while those with PD were more likely to have deficits in all areas than participants without PD, but mostly showed normal Perceptive aptitude. Although our findings were generally consistent with prior observations from other studies (Keloth et al, 2019; Lazarotto et al, 2020; Lee et al, 2018; Stegemöller et al, 2019; Stuart et al, 2019; Xu et al, 2018) our use of the MSOA permitted greater specification in describing motor aptitude differences of older adults with and without PD. Furthermore, participant gender and age group were associated with these motor aptitude outcomes, regardless of the presence or absence of PD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that most participants without PD had normal or unimpaired motor aptitude levels, while those with PD were more likely to have deficits in all areas than participants without PD, but mostly showed normal Perceptive aptitude. Although our findings were generally consistent with prior observations from other studies (Keloth et al, 2019; Lazarotto et al, 2020; Lee et al, 2018; Stegemöller et al, 2019; Stuart et al, 2019; Xu et al, 2018) our use of the MSOA permitted greater specification in describing motor aptitude differences of older adults with and without PD. Furthermore, participant gender and age group were associated with these motor aptitude outcomes, regardless of the presence or absence of PD.…”
Section: Discussionsupporting
confidence: 89%
“…As would be expected from the neurodegenerative characteristics of PD (Postuma et al, 2015), our much smaller sample of participants with PD had a lower motor aptitude performance than those without PD. Other studies have also shown that individuals with PD perform more poorly on simple motor activities such as walking and on more complex activities such as writing or turning on one's axis than do older adults without the disease (Stegemöller et al, 2019;Stuart et al, 2019). These motor deficits are related to bradykinesia, tremors, postural instability, and stiffness, which are frequent PD symptoms (Armstrong & Okun, 2020;Balestrino & Schapira, 2020).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions may range from emphasizing accuracy or speed to displaying intermittently flashing template lines for tracing. These deviations from a patient's previously completed drawing tasks will likely allow for easier differentiation between PD patient and control data [54,55].…”
Section: Task Variationmentioning
confidence: 99%
“…As previously stated, previous research has found that stress negatively impacted skilled reaching in a PD rat model , and that a stressful environment negatively impacted gait in persons with PD . Further support, is demonstrated by correlations between finger tapping and performance of more complex tasks such as purdue peg board (Müller, Schäfer, Kuhn, & Przuntek, 2000), buttoning , handwriting (Stegemöller, Zaman, & Uzochukwu, 2019), and posture and postural instability (Stegemöller, et al, 2016).…”
Section: Discussionmentioning
confidence: 96%